Exogenous 6‐benzyladenine treatment alleviates cold stress in early japonica rice at booting in Northeast China. (4th August 2022) - Wang, Shiqiang; Yang, Shanwei; He, Dengmei; Yi, Yuzhuo; Fu, Yongming; Yin, Dawei; Zhao, Haihong; Xiao, Changliang
Abstract: Rice ( Oryza sativa L.) plants are most sensitive to chilling injury at booting, where cold affects a substantial decline in the seed‐setting rate (SSR). 6‐Benzyladenine (6‐BA) alleviates cold stress in seedlings; however, little is known about the effects of 6‐BA on alleviating cold stress at booting. Plants of early japonica rice cultivars Kenjiandao6 (K6) and Kongyu131 (K131) were sprayed with 6‐BA at concentrations of 0, 0.2, 2, 20, 200, and 500 mg L −1 at booting and were then subjected to cold water stress (16 °C) for 5 d. The optimal 6‐BA concentration was found to be 20 mg L −1 . 6‐Benzyladenine treatment improved the peroxidase (POD) activity in two cultivars and superoxide dismutase activity in K6, delayed chlorophyll degradation, maintained the K, P, and N contents in the two cultivars and the soluble protein content in K6, and suppressed the accumulation of malondialdehyde (MDA) under cold stress. 6‐Benzyladenine increased the N and P contents and POD activity to greater degree in K6 than in K131. 6‐Benzyladenine increased yield in K131, mainly by improving the SSR in the distal and middle parts of the panicle, and the number of filled grains (NFG) from the middle and basal parts of the panicle. However, 6‐BA increased yield in K6 mainly by improving the SSR and the NFG per panicle. Exogenous 6‐BA is effective for maintaining rice physiology and yield under cold stress at booting. The less cold‐tolerant cultivar K6 was more sensitive to the effects of 6‐BA and displayed better results than did the more cold‐tolerant cultivar K131. Core Ideas: The optimal 6‐benzyladenine concentration was found to be 20 mg L −1 under cold stress in early japonica rice at booting. 6‐Benzyladenine at 20 mg L −1 effectively reduced the physiological and metabolic damage in rice due to cold stress at booting. 6‐Benzyladenine increased the cold resistance of 'Kongyu131' mainly by improving the peroxidase activity, chlorophyll, N, P, and K contents. 6‐Benzyladenine enhanced a resistance of 'Kenjiandao6' mainly by improving superoxide dismutase and peroxidase activities, soluble protein, chlorophyll, N, P, and K content. The effect of 6‐benzyladenine was higher in the less cold tolerant variety Kenjiandao6 than in Kongyu131 under cold stress.